The Influence of Work Life Balance and Work Engagement on Work Productivity with Work Motivation as a Mediating Variable on Employees of the West Nusa Tenggara Province Language Center - M. Rozi Fatwa Ilham; Muttaqillah (LP2M IAIN Palopo, 2026)
This study analyzes the influence of Work Life Balance (WLB) and Work Engagement (WE) on Work Productivity with Work Motivation as a mediating variable in 45 employees of the West Nusa Tenggara Provincial Language Center. The phenomenon of low productivity is caused by the imbalance of work and personal roles amidst the high demands of language development. This type of causal associative research with a quantitative approach using a Likert questionnaire, tested for validity and reliability, and analyzed by multiple regression and the Sobel test via SPSS 27. The population of all employees was used as a census sample. The results show that WLB and WE have a significant positive effect on productivity directly (t>2.019, p<0.05) and indirectly through motivation (Z>1.96, p<0.05), with a high average score (productivity 4.14; motivation 4.17). The conclusion recommends flexible work policies to improve motivation and performance in public organizations